Basic Science teaching in Nursery teaching: a challenging panorama in education research - Azevedo, Adriana Medeiros Sales de; Akerman, Marco (ABCS Health Sciences, 2015)
This article aims to investigate what has been produced on research in Nursing education regarding to science education, teaching of specific disciplines on Health Sciences, their strategies and impact. The method of data collection was conducted through search in the platforms SciELO and LILACs only in Portuguese. The results show that even descriptors that deal squarely on education and science bring a large volume of articles unrelated to the search keywords, and even refining it the results are much lower in volume compared to other types of production in nursing education. The results suggest the existence of a large potential for expansion in the production of scientific research in Nursing education in the areas of Basic Sciences of Health in Brazil.